The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2147/tcrm.s88911
|View full text |Cite
|
Sign up to set email alerts
|

Use of direct oral anticoagulants for the prevention and treatment of thromboembolic disease in patients with reduced renal function: a short review of the clinical evidence

Abstract: BackgroundThe use of direct oral anticoagulants (DOACs) is restricted by the limitations of clinical trials guiding therapy for patients with renal impairment, as many of these trials excluded patients with severe renal impairment. There are currently four agents available: dabigatran, rivaroxaban, apixaban, and edoxaban. The purpose of this review was to 1) describe current recommended dosing for each DOAC and published postmarketing data, including case reports, on the use of these agents in the renally impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Our findings are consistent with several reviews on the use of DOACs in the treatment of VTE among CKD patients (including elderly patients). 30,31 Among patients with moderate kidney impairment (CrCl = 30-49 mL/min), Parker and Thachil 32 also concluded in their review that DOACs are noninferior to VKA therapy in terms of efficacy in acute, symptomatic VTE. Our systematic review findings are also similar to the meta-analysis of 26 872 patients in the 6 RCTs comparing DOACs with VKAs for treatment of acute symptomatic DVT, PE, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with several reviews on the use of DOACs in the treatment of VTE among CKD patients (including elderly patients). 30,31 Among patients with moderate kidney impairment (CrCl = 30-49 mL/min), Parker and Thachil 32 also concluded in their review that DOACs are noninferior to VKA therapy in terms of efficacy in acute, symptomatic VTE. Our systematic review findings are also similar to the meta-analysis of 26 872 patients in the 6 RCTs comparing DOACs with VKAs for treatment of acute symptomatic DVT, PE, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the case of using DOACs in atrial fibrillation for the CKD/dialysis population, there is still a lack of efficacy and safety data of using these agents for treatment of VTE in HD patients or those with severe kidney impairment. 31 Reduced doses of apixaban may be an option for VTE treatment if cautiously used in patients with moderate to severe kidney impairment. A recommendation table to help clinicians and practitioners in applying the findings from this systematic review is found in the Supplementary Material Table S3.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
“…In spite of data suggestive of their usefulness vs. classical warfarin in the general population [ 462 ], to the best of our knowledge, insufficient information is available about their application and the health-economic impact in CKD. In addition, they should be used with care in CKD, as their renal elimination may be hampered progressively as renal function deteriorates [ 463 , 464 ].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Risks may be increased in case of renal dysfunction 277 , and concomitant medications or age may also affect bleeding. Non-steroidal anti-inflammatory drugs 278,279 did not increase the risk of bleeding for dabigatran 278 , and age older than 75 280 showed lower risk of bleeding with anti-Xa medications than with LMWH (OR = 0.71).…”
Section: - Which Vte Prophylactic Agent Used In Patients Undergoing T...mentioning
confidence: 99%